2010
DOI: 10.1007/978-1-60327-299-5_18
|View full text |Cite
|
Sign up to set email alerts
|

Near-Infrared Optical Proteolytic Beacons for In Vivo Imaging of Matrix Metalloproteinase Activity

Abstract: The exuberant expression of proteinases by tumor cells has long been associated with the breakdown of the extracellular matrix, tumor invasion, and metastasis to distant organs. There is both epidemiological and experimental data that support a causative role for proteinases of the matrix metalloproteinase (MMP) family in tumor progression. Optical imaging techniques provide an extraordinary opportunity for non-invasive “molecular imaging” of tumor-associated proteolytic activity. The application of optical pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 12 publications
1
28
0
Order By: Relevance
“…Paclitaxel was attached to the N-terminus of the peptide using published procedures to give ND PXL (Majoros et al, 2006). Our MMP-beacons, originally on a polyamidoamine (PAMAM) scaffold, include a two-color FRET probe with sensor and reference dyes for quantifying MMP activation (McIntyre et al, 2004; McIntyre and Matrisian, 2009; McIntyre et al, 2010). For these studies, novel beacons were made from AVRWLLTAC peptide attached to the ND as will be described in detail elsewhere (Scherer et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Paclitaxel was attached to the N-terminus of the peptide using published procedures to give ND PXL (Majoros et al, 2006). Our MMP-beacons, originally on a polyamidoamine (PAMAM) scaffold, include a two-color FRET probe with sensor and reference dyes for quantifying MMP activation (McIntyre et al, 2004; McIntyre and Matrisian, 2009; McIntyre et al, 2010). For these studies, novel beacons were made from AVRWLLTAC peptide attached to the ND as will be described in detail elsewhere (Scherer et al, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Phantoms were prepared with either the sensor or reference dye bound to PAMAM, (McIntyre et al, 2004; McIntyre et al, 2010), or ND PXL -ND PB (not protease treated) or MMP9-treated ND PXL -ND PB , or ND PB without ND PXL , each in matrigel and injected subcutaneously into nu/nu mice, to create a localized phantom (Fig. 2A).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Currently, PET or SPECT imaging of MMPs is still at a preliminary stage and no related clinical study has been reported yet. Compared with blooming studies in fluorescence imaging of MMPs [135], PET or SPECT imaging of MMPs enabled the researchers to observe the MMP distribution or activation in deeper tissues, but usually resulted in lower target-to-background ratio. In order to improve the PET or SPECT tracers for imaging of MMP, chemical modification of existing MMPIs to decrease the non-specific binding or using anti-MMP antibodies could be alternative strategies.…”
Section: Pet or Spect Imaging Of Vascular Targets In Cancermentioning
confidence: 99%
“…The injectable probes that have been used to measure protease activity in tumors include autoquenched protease substrates that fluoresce upon cleavage (Weissleder et al, 1999), proteolytic beacons that lose FRET upon cleavage (e.g. McIntyre et al, 2010;Scherer et al, 2008) and fluorescently labeled activatable cell-penetrating peptides (ACCPs) that translocate into cells upon cleavage (Olson et al, 2009;Olson et al, 2010). The disadvantage of these probes is that chemical knowledge is required to synthesize them, although recent commercialization of some of these probes has overcome this problem.…”
Section: Intravital Imaging Of Proteins Proteases Signaling Pathwaymentioning
confidence: 99%